Utility of Recipient Cardiothoracic Ratio in Predicting Delayed Chest Closure after Heart Transplantation - Sukhavasi, Amrita; Ahmad, Danial; Austin, Melissa; Rame, J. Eduardo; Entwistle, John W.; Massey, Howard T.; Tchantchaleishvili, Vakhtang (The Thoracic and Cardiovascular Surgeon, 2023)
Background Predicted cardiac mass (PCM) has been well validated for size matching donor hearts to heart transplantation recipients. We hypothesized that cardiothoracic ratio (CTR) could be reflective of recipient-specific limits of oversizing, and sought to determine the utility of donor to recipient PCM ratio (PCMR) and CTR in predicting delayed chest closure after heart transplantation.Methods A retrospective review of prospectively collected data on 38 consecutive heart transplantations performed at our institution from 2017 to 2020 was performed. Donor and recipient PCM were estimated using Multi-Ethnic Study of Atherosclerosis predictive models. Receiver operating characteristic analysis was performed to determine the discriminatory power of the ratio of PCMR to CTR in predicting delayed sternal closure.Results Of the 38 patients, 71.1% (27/38) were male and the median age at transplantation was 58 (interquartile range [IQR]: 47–62) years. Ischemic cardiomyopathy was present in 31.6% of recipients (12/38). Median recipient CTR was 0.63 [IQR: 0.59–0.66]. Median donor to recipient PCMR was 1.07 [IQR: 0.96–1.19], which indicated 7% oversizing. Thirteen out of 38 (34.2%) underwent delayed sternal closure. Primary graft dysfunction occurred in 15.8% (6/38). PCMR/CTR showed good discriminatory power in predicting delayed sternal closure [area under the curve: 80.4% (65.3–95.6%)]. PCMR/CTR cut-off of 1.7 offered the best trade-off between the sensitivity (69.6%) and specificity (91.7%).Conclusion CTR could be helpful in guiding the recipient-specific extent of oversizing donor hearts. Maintaining the ratio of PCMR to CTR below 1.7 could avoid excessive oversizing of the donor heart.
Keywords: heart transplantation; cardiothoracic ratio; delayed sternal closure; DSC; HTx; predicted cardiac mass